Influence of Customer Loyalty, Consumer Animosity and Purchase Intention on Consumer Ethnocentrism - Bada, Bukola Victoria; Onuoha, Chibuzor Uchenna (European Scientific Journal, ESJ, 2018)
The study examined the influence of customer loyalty, consumer animosity and purchase intention on consumer ethnocentrism. The research was a cross-sectional survey which made use of purposive sampling technique to select 196 (males = 109; females = 87) undergraduates from two public universities in Nigeria. Standardized scales that measured customer loyalty, consumer animosity, purchase intention and consumer ethnocentrism were adapted into a questionnaire format and used for data collection after theywere revalidated for cultural relevance. Three hypotheses were tested in the study. Results showed significant positive relationships among customer loyalty, consumer animosity, purchase intention and consumer ethnocentrism (p<.01). Additional result revealed significant independent and combined influence of customer loyalty, consumer animosity and purchase intention on consumer ethnocentrism. However, gender did not influence consumer ethnocentrism. It was concluded that customer loyalty, consumer animosity and purchase intention were strongly related to consumer ethnocentrism. The findings of the study were discussed alongside recommendation.